Islamic Education Learning Management in Creating Religious Culture in Integrated Islamic Elementary Schools - Ahmad Jiyad; Fathur Ramadhan (Lembaga Yasin AlSys, 2025)
This systematic literature review analyzes the management of Islamic Religious Education (Pendidikan Agama Islam/PAI) learning in Integrated Islamic Elementary Schools (Sekolah Dasar Islam Terpadu/SDIT) in Indonesia as a strategic mechanism for constructing substantive religious culture amid the challenges of globalization and secularization. Employing thematic content analysis of sources from Scopus, Google Scholar, DOAJ, and institutional repositories (2010–2025), the study synthesizes evidence on how religious culture is constructed through habituation practices (such as congregational prayers and tadarus), the benefits of PAI learning management (including strengthened discipline and emotional resilience through optimized resource use), and key challenges (such as deficits in teacher training, digital distractions, and gaps in Merdeka Curriculum integration). The findings show that structured PAI management functions—planning, organizing, actuating, and controlling—serve to bridge sharia principles with modern pedagogy, fostering holistic character formation while addressing tendencies toward exclusivism and responding to infrastructural constraints through solutions such as blended learning, professional development workshops, and parental collaboration. Theoretically, the study advances Islamic education discourse by hybridizing a tawhid-based habitus with contemporary educational models; practically, it offers policy-oriented insights for SDIT leaders and for Indonesia’s Ministries of Religious Affairs and Education. The review recommends that future empirical research validate these conclusions using mixed-methods designs in diverse institutional contexts to assess the long-term impact of PAI learning management on students’ religious identity.